The Mapuche people in Vaca Muerta, Argentina - Duarte, Melisa Cabrapan (Anthropos (Ljubljana), 2025)
In this paper, I contextualize the conflicts that characterize Vaca Muerta in northern Patagonia, Argentina, a geological formation of unconventional hydrocarbon reservoirs that over the past decade has become an area of national and international energy interest. How ever, social discontent, particularly from the Mapuche communities pre-existing in the area and forming the Regional Coalition Xawvn Ko of the Mapuche Confederation of Neuquén, has led these communities to express their repudiation of the oil companies and the governments in power due to the consequences of fracking: environmental damage, territorial dispossession, the criminalization of the Mapuche people, and the impoverishment of the local society. In this context, I examine the persecution of these communities and the increase in repressive measures under the current government. I also describe and analyse the inter-communitarian resurgence and resistance and how these create new political aesthetics to confront extractivism.
Keywords: aesthetics of resistance; criminalization; ekstraktivizem; estetika odpora; extractivism; kriminalizacija; Mapuche people; Mapuči, Vaca Muerta, ekstraktivizem, kriminalizacija, estetika odpora; Vaca Muerta